An Observational Study of Acquired EGFR T790M-Dependent Resistance to EGFR-TKI Treatment in Lung Adenocarcinoma Patients in Taiwan - Wu, Shang-Gin; Chiang, Chi-Lu; Liu, Chien-Ying; Wang, Chin-Chou; Su, Po-Lan; Hsia, Te-Chun; Shih, Jin-Yuan; Chang, Gee-Chen (Frontiers in Oncology, 2020)
In Taiwan, epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (EGFR-TKIs), gefitinib, erlotinib, and afatinib are served as first-line therapy for non-small lung cell cancer (NSCLC) patients with EGFR sensitizing mutations. However, the majority of patients who initially respond to EGFR-TKIs, progress through acquiring EGFR T790M mutations (T790M), which is the most common resistant mechanism. Patients with T790M gain the opportunity of subsequent treatment with third-generation EGFR-TKI, osimertinib. This study aimed to evaluate the association between prior EGFR-TKI therapy and incidence of acquired T790M resistance in lung adenocarcinoma patients who have progressed on first/second-generation EGFR-TKI therapy. This retrospective study included lung adenocarcinoma patients who had a radiographically-confirmed progressive disease under EGFR-TKI treatment and had re-biopsy samples for T790M testing from seven medical centers in Taiwan from June 2013 to December 2018. Patients harboring de novo T790M or using more than one EGFR-TKI were excluded. Of the 407 patients enrolled, the overall T790M acquisition rate was 52.8%. The patients treated with gefitinib, erlotinib, or afatinib had a statistically significant difference in the T790M rates (59.9%, 45.5%, and 52.7%, respectively; p = 0.037) after disease progression. Patients with common baseline EGFR mutations (Del-19 and L858R) (p = 0.005) and longer treatment duration with EGFR-TKIs (p < 0.001) had higher chances of T790M acquisition. Multivariate logistic regression analysis further showed that patients with common baseline EGFR mutations, gefitinib (compared to erlotinib) administration, and longer treatment duration with EGFR-TKIs had higher T790M incidence. There was no significant difference in the incidence of acquired T790M between different re-biopsy tissue samples or complications. In conclusion, this study showed that patients who progressed from gefitinib treatment, bearing common EGFR mutations, and with longer EGFR-TKI treatment duration had increased incidence of T790M acquisition and, therefore, were suitable for subsequent osimertinib treatment.